2005
DOI: 10.1590/s0004-282x2005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and scholing on the performance in a modified Mini-Mental State Examination version: a study in Brazil Northeast

Abstract: -Perf o rmance in cognitive tests can be influenced by age and education level. In developing countries, formal education is limited for most people. Application of the Mini-Mental State Examination (MMSE) test, in its original version could have an adverse effect on the evaluation of low educated and elderly individuals. O b j e c t i v e: To assess the cognitive perf o rmance of low and middle educated old people in a modified version of the adapted to portuguese language MMSE. M e t h o d: A study was carr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
1
10
0
5
Order By: Relevance
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
“…Scores on MMSE are greatly influenced by age and education level (13)(14)(15). Cognitive impairment and dementia have been associated with rural dwellers (16), increased rates of hospitalization (17,18), increased risk for falls (19,20), increased prevalence of fear of falling (21,22), diabetes mellitus (23,24), depression (17,25), and dependence in activities of daily living [ADL] (26).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos nacionais e internacionais mostraram que o aumento da idade e o baixo nível educacional estão relacionados ao pior funcionamento cognitivo em idosos (Argimon & Stein, 2005;Bertolucci, Brucki, Campacci, & Juliano, 1994;Brito-Marques & Cabral-Filho, 2005;Brucki & Rocha, 2004;Erven & Janczura, 2004;Foss, Vale, & Speciali, 2005;Meguro et al, 2001;Nitrini, 1999;Ostrosky-Solsi, Ardila, Rosselli, Lopez-Arango, & Uriel-Mendoza, 1998;Rosselli & Ardila, 2003). Por outro lado, os estudos são contraditórios sobre a associação do desempenho cognitivo com a variável gêne-ro.…”
unclassified
“…There was no correlation between both scales and education 14,15 . There is a large amount of research on the correlation between education and cognitive per- formance, but our results could have two explanations: the tasks in these two scales are quite simple and there is a clear floor effect in control or less advanced dementia patients; the education bias might disappear at a relatively early stage of dementias.…”
Section: Discussionmentioning
confidence: 75%